Providing financial protection in health for low-income populations: a comparison of health financing designs in East Asia - Qian Zhang; Julia Shu-Huah Wang; Alex Jingwei He; Chenhong Peng; Aya Abe; Inhoe Ku; Irene Y.H. Ng; Xi Zhao (International Journal for Equity in Health)
Abstract Background Fighting illness and poverty are intertwined objectives in global development. In recent decades, health financing reforms across many nations have enhanced financial protection for low-income populations and promoted health equity for all citizens. However, prior cross-national comparative studies predominantly focused on examining financing structures or social health insurance (SHI) schemes, neglecting financing schemes targeting the poor, such as medical financial assistance (MFA). This study comparatively explores the design of health financing schemes and financial protection outcomes for low-income populations across six societies in East Asia: mainland China, Hong Kong, Taiwan, Japan, South Korea, and Singapore. Methods We assess the design of health financing schemes from the dimensions of income-based eligibility, population coverage, and benefit generosity. Policy information was collected from official websites and policy reports. To compare financial protection outcomes, we derived the data through the “model family approach” and jurisdiction-level statistics and simulated catastrophic health spending of lung cancer for individuals across four income levels: (1) no income; (2) earning minimum wage; (3) earning half the national/regional average wage; and (4) earning the national/regional average wage. Results We find that health financing schemes in Taiwan and Hong Kong are generous and inclusive for general populations, while Japan, South Korea, and Singapore’s financing schemes are protective and offer relatively generous benefits for vulnerable groups. In contrast, mainland China provides limited benefits in SHI and MFA schemes. Health financing schemes reduce the financial burden to varying degrees, with Taiwan, Hong Kong, and South Korea providing financial protection for low-income populations to a higher degree, followed by Japan, Singapore, and mainland China. Notably, our findings highlight inequities for individuals earning half the average wage in Singapore, mainland China, and Japan (and to a lesser extent in Taiwan, Hong Kong and Korea), as these groups face higher risks of catastrophic health spending compared to other income groups. Conclusions Our findings further the understanding of health financing designs in East Asia. We also provide evidence for governments to enhance financial protection for low-income populations, particularly near-poor groups, to achieve more equitable health financing arrangements.